Strategies for blood collection and optimization of the blood supply chain during the COVID‐19 pandemic in Greece. (7th November 2020) - Politis, Constantina; Richardson, Clive; Hassapopoulou‐Matamis, Helen; Politi, Lida; Hatziagapiou, Kyriaki; Grouzi, Elisavet; Bollas, George; Soulakis, Vassilios; Pagonis, Sotirios; Nomikou, Efrosini; Constantinidis, Eleftherios; Zervou, Eleftheria
Abstract : Background: Early action in Greece restricted COVID‐19 to Europe's second lowest rate of cases and deaths. However, the pandemic significantly reduced blood supply. We present counter‐measures implemented in Greece, analyse data retrieved from blood services in the period from 1st February to 14th May 2020, and examine the pandemic's impact on blood supply and demand. Materials and Methods: Sixteen blood services provided their aggregate blood collection, broken down by whole blood or platelet apheresis, and by location (inside or outside the hospital), every two weeks during the study period. Aggregate donor demographics were recorded where available. Total collection was compared by period and location. Results: Total blood collection declined by 36% during the study, especially (65%) on the premises of the blood services. However, outpatient blood sessions organized under the 'All Together We Can' programme had an important impact, and supply and demand were balanced by the end of the study. Conclusion: The strategy of blood sessions and blood drives in outpatient facilities, rather than the in‐hospital environment, was successful in securing a balance between blood collection and demand. Significant shortages in supply were reported, as expected during pandemics; however, the blood inventory was managed efficiently and a demand‐based blood collection and allocation plan was developed to achieve adequate blood supply. Stringent transfusion criteria and surveillance for emergency usage of blood components were used to help in this. An active surveillance system for emergency procurement and use of blood components was also designed to optimize the blood supply chain.